Yo Bikes : pricing for electric scooters - Sahay, Arvind, (SAGE Knowledge. Cases., 2017)
Pratap Halve, the SBU Head for Electric Scooter division of Thermoelectric sat in his office in Thaltej, Ahmedabad wondering about what approach he should adopt for pricing for marketing of electric scooters sold under the Yo Bike brand name. Sales had already gone above 30,000 in the previous year and he had a target of selling more than a 100,000 during FY 2008-09. However, sales were running well below target, partly due to an economic slowdown and partly due to a hesitation on the part of the consumer to buy an electric scooter in larger numbers. It was a cool December afternoon in 2008. Some important holidays were coming up in the calendar over the next three months that were traditionally used by Indians as an auspicious time to make purchases and Halve was to meet his Managing Director to consider plans for Yo Bikes.